Double-barrel entanglement of intracranial Enterprise stents resulting from undetected incomplete stent apposition. (9th January 2012) - Heller, Robert S; Safain, Mina; Malek, Adel M
Abstract : Objective: Although intracranial stents have expanded the spectrum of aneurysms amenable to coiling, closed cell design variants can be prone to incomplete stent apposition around tightly curved arterial bends. A case is presented illustrating the technical ramifications of this phenomenon during subsequent treatment. Clinical presentation: A 49-year-old woman who had previously undergone Enterprise (closed cell design) stent mediated coiling of a wide necked ophthalmic carotid artery aneurysm was noted to harbor residual central filling on follow-up imaging, and was scheduled for additional embolization. Intervention: During retreatment, performed with a second concentrically placed Enterprise and further coil packing using the jailing technique, the proximal portion of the second Enterprise stent failed to expand as expected. C-arm cone beam CT (CBCT) revealed the second stent to have been navigated into and out of the orphaned lumen created by the incompletely apposed first Enterprise stent at the carotid siphon. This stent entanglement resulted in the formation of a trapped proximal double-barrel lumen in the curved segment and resolution to a single barrel lumen in the distal straight segment of the parent vessel facing the aneurysm neck. Conclusion: Caution is urged when navigating around curved vessel segments through previously deployed intracranial stents, which may be incompletely apposed to the vessel wall, to avoid deleterious and potentially catastrophic entanglement. CBCT imaging may be helpful in delineating the spatial relationship of previously deployed intracranial stents during subsequent endovascular navigation.